RESPON GURU DAN SISWA TERHADAP PENGGUNAAN LKS BERBASIS MULTIPLE INTELLEGENCES - dian ika kusumaningtyas (Universitas Kanjuruhan Malang, 2019)
The applied learning should facilitate in maximizing the intelligence possessed by students. To maximize students' intelligence needed teaching materials that can support students in carrying out activities. Student books given by the government are not enough to maximize student intelligence. So that it takes the development of worksheets that can maximize the intelligence of students as a whole, it requires multiple intelligence based LKS. The application of this LKS when tested to students requires a response from students, because students are the users of the LKS. The method used in this study is descriptive qualitative research, data collection is done by observation, documentation, and questionnaires, then data analysis is performed. The results of this study are teacher responses and student responses are LKS makes students happy because LKS is easy to understand, varied activities that support maximizing intelligence, LKS is interesting and directs students more active. In addition, LKS utilizes the environment as a learning resource for students. Suggestions conveyed by teachers and students for the improvement of LKS are in terms of language writing and terms need to be clarified.